ANALISIS PERANCANGAN PROTOTYPE INTERNET of THINGS (IoT) PADA STMIK NEUMANN - Andreas Paniroy Girsang; Bersama Sinuraya (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
The use of computers in the future can dominate human work and defeat human computing such as controlling electronic equipment remotely using internet media, Internet of Things (IoT) allows users to manage and optimize electronics and electrical equipment using the internet. This makes these machineswork alone and humans can enjoy the work of these machines without having to bother managing them. The workings of the Internet of Things (IoT) are quite easy. Every object must have an IP Address. After an object has an IP address and is connected to the internet, the sensor is also installed. Currently atSTMIK NEUMANN has complete facilities for each classroom and lab room where air conditioners, lamps and other electronic devices are still manually controlled so that staff sometimes forget to turn off air conditioners, lights and other electronic devices. Therefore, by utilizing the internet network atSTMIK NEUMANN the author tries to make a simulation of the Internet of Things (IoT) to make it easier for staff to control electronic devices in STMIK NEUMANN.